2012
DOI: 10.1016/s1836-9553(12)70068-1
|View full text |Cite
|
Sign up to set email alerts
|

Stretching before sleep reduces the frequency and severity of nocturnal leg cramps in older adults: a randomised trial

Abstract: NCT01421628.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 14 publications
4
45
1
5
Order By: Relevance
“…In this context it should be noted that evidence on the effectiveness of stretching to prevent cramps is contradictory. While the study from Hallegraef et al [12] found a reduced frequency and severity of nocturnal leg cramps in older adults, Coppin and colleagues [11] concluded that stretching failed to improve those items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it should be noted that evidence on the effectiveness of stretching to prevent cramps is contradictory. While the study from Hallegraef et al [12] found a reduced frequency and severity of nocturnal leg cramps in older adults, Coppin and colleagues [11] concluded that stretching failed to improve those items.…”
Section: Discussionmentioning
confidence: 99%
“…This trial, though impaired by serious limitations in design, assessed the effectiveness of daytime calf muscle stretching in preventing nighttime muscle cramps [11]. After publication of the Cochrane review, one additional randomized controlled trial [12] published supporting evidence of the effectiveness of calf and hamstring stretching before sleep on nocturnal leg cramps. This approach was the subject of debate in several editor's correspondences published by the Journal of the American Medical Association [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…The patient wished minimal intervention and decided to use prescribed stretching exercises of her lower legs for prevention of her nocturnal leg cramping. 8 Evening lower leg stretching exercises for nocturnal leg cramps, and position therapy for sleep-disordered breathing have improved patient's sleep quality. …”
Section: Discussionmentioning
confidence: 99%
“…7 However, a six-week randomized trial with concealed allocation and intention-to-treat analysis published after the systematic review showed significant decreases in both the frequency (mean difference 1.2 cramps [95% CI 0.6-1.8] per night) and severity (mean difference 1.3 cm [95% CI 0.9-1.7] on 10-cm visual analog scale) of nocturnal leg cramps with nightly calf and hamstring stretches. 8 Although there is consensus that quinine should not be used routinely for nocturnal leg cramps, a complete ban would be draconian. The Medicines and Healthcare Products Regulatory Agency in the United Kingdom provides sound practice advice, in my opinion.…”
Section: Key Pointsmentioning
confidence: 99%